THE MISUSED OF LETTER OF CREDIT IN ACCORDING WITH UCP-500 PRACTICE IN THE PROCESS OF DOCUMENTS IN BANKING AND CUSTOMS PERSPECTIVE - Jummaidi Saputra (JOURNAL OF LAW AND GOVERNMENT SCIENCE, 2015)
In the trade transaction which are  done either individually or inter-State / bilaterally and in multilateral, guaranteeing is a must to do. Guaranteeing the transaction can be facilitated through  a sale contract (purchase agreement). If this is undertaken, for the realizations, it is implemented in the a form of trade relation in order to get an opinion of the guarantee from the two sides of both seller (exporter) and the buyer (importer) to do an agreement by issuing a relationship between Banks which is called the issuing of credit letter of credit  L / C). It aims to ensure the payment transaction and delivery of goods. The arrangements of Guaranteeing of a transaction must conform to the provisions of the Law as well as the international trade system.  Irregularities and misuse of the L / C will have to be resolved by law and applicable regulation. In the case of misused of L / C at Bank BNI-46 Jakarta, should be resolved according to the law,  alleged parties should face a clear sanction. A wrong procedure which presents  filed documents as if it is true was undertaken, disregard the fact  that case was an absolute crime which must be punished severely in order to create a deterrent effect for these wrongdoers.Keywords : Letter of Credit, UCP-500 Practice, Banking, Customs